Byblos in the late bronze age : interactions between the Levantine and Egyptian worlds - Kilani, Marwan, 1987- (Studies in the Archaeology and History of the Levant;, 2020)
"In Byblos in the Late Bronze Age, Marwan Kilani reconstructs the "biography" of the city of Byblos during the Late Bronze Age. Commonly described simply as a centre for the trade of wood, the city appears here as a dynamic actor involved in multiple aspects of the regional geopolitical reality. By combining the information provided by written sources and by a fresh reanalysis of the archaeological evidence, the author explores the development of the city during the Late Bronze Age, showing how the evolution of a wide range of geopolitical, economic and ideological factors resulted in periods of prosperity and decline. .